Effects of High Dose of Atorvastatin for Preventing Periprocedural Ischemic Brain Damage in Patients Undergoing Carotid Artery Stenting (PICAS) in China: A Randomized Controlled Clinical Trial - Wang, Haipeng; Wang, Junjie; Lu, Jun; Wang, Daming (Frontiers in Neurology, 2020)
Background: Research conducted in Western countries has suggested that high-dose statin therapy can lead to the regression of carotid atherosclerotic plaques and can reduce periprocedural ischemic complication rates in individuals undergoing carotid artery stenting (CAS). However, whether this same therapeutic approach is of value in patients of Chinese ethnicity is not as well established. Methods: This is a single-center, prospective, parallel-controlled, intervention-based efficacy study that will enroll a total of 130 Chinese patients with cervical carotid stenosis who are scheduled to undergo CAS. These patients will be randomly divided into a routine treatment group and a high-dose atorvastatin group. Individuals in the routine treatment group will be administered standard of care 20 mg/day atorvastatin treatment. Individuals in the high-dose atorvastatin group will be administered 80 mg/day atorvastatin for three days prior to and following CAS. The primary endpoint of this study will be the cumulative incidence of new cerebral ischemic lesions with or without neurological symptoms within a 1 to 7-day period following CAS, and the cumulative incidence of transient ischemic attacks (TIAs) or ischemic stroke within a 30-day period following CAS. Discussion: This study is the first to assess whether high-dose atorvastatin treatment is capable of reducing the incidence of perioperative cerebral ischemic injury in patients of Chinese ethnicity undergoing CAS. These results will offer evidence regarding which statin treatment regimens are more appropriate when treating Chinese patients undergoing CAS in an effort to minimize their risk of any perioperative cerebral ischemic injury.